Avaliação da memória emocional em camundongos: efeito da injeção de midazolam na substância cinzenta periaquedutal - Pereira, Barbara Caetano (Universidade Federal de São Carlos, 2012)
Several studies have shown that benzodiazepines (BDZ) in periaqueductal gray (PAG) can produce anxiolytic-like effects in different animal models of anxiety. In addition, BDZ drugs also impair learning and memory performance in rodents. Despite the known role of PAG in modulated defensive behaviors in animal models, little is known about its role in modulated of emotional memory. In this sense, the objective of this study was to investigate the effects of midazolam, injected into the PAG, on the acquisition, consolidation and retrieval of aversive memory. For this, we used male mice of the Swiss-Albino weighing between 25-30g (n=7-11). After stereotactic surgery with implantation of a cannula in the PAG, the animals on the test day were divided into three experiments for later exposed to the test "step-down" (SD), as follows: Experiment 1, intra-PAG with saline and midazolam (MDZ) at doses of 3.0 and 30 nmol/0.1μl, in condition of pre-training to evaluate the acquisition of aversive memory; Experiment 2 was like Experiment 1, except for the condition of the injection pretest to evaluate the retrieval of aversive memory; Experiment 3 was like Experiment 1, except for the condition of injection post training to evaluate the consolidation of aversive memory. The animals were trained in the inhibitory avoidance task that was to distributed the animals into two groups: N/Sh - without exposure to shock, W/Sh - with exposed to shock (0.5 mA) for 10 seconds, to record the latency of descent (L1). Twenty-four hours later, each animal was exposed again on SD to record latency (L2), but without shock. The results were evaluated by analysis of variance (ANOVA) of three factors (Factor 1: condition; Factor 2: pre-treatment Factor 3: treatment) for L1 and L2. The results showed that there was an increase of L2 after exposure of mice to SD without shock, confirming that the aversive stimulus (shock) was strong enough to promote facilitation of aversive memory. The two doses (3.0 and 30 nmol) of MDZ intra-PAG decreased the risk assessment of mice, characterized by the fast descent of the platform in L1. This result suggests that GABAbenzodiazepine agonist impaired the acquisition, consolidation and retrieval of aversive memory in mice. Taken together, these results suggest that GABAA receptors within PAG seem to modulate the response related to aversive memory induced by shock.
Keywords: Neurociência; Memória; Substância cinzenta periaquedutal; Ansiedade; Esquiva inibitória; Camundongos; Midazolam; Memory; Anxiety; Periaqueductal gray matter; Midazolam; Avoidance inhibitory; Mice; CIENCIAS HUMANAS::PSICOLOGIA